SEKTOR INFORMAL DAN KEMAJUAN TEKNOLOGI INFORMASI DI INDONESIA - Sita Dewi; Dwi Listyowati; Bertha Elvy Napitupulu (JURNAL MITRA MANAJEMEN, 2020)
AbstractThe population of Indonesia has increased. The laborforce of Indonesia has increased alongside the increasing population, but the growth oknowf employment opportunities (job demand) is not on par with the growth of laborforce. As a result, an unorganized employment opportunity was made known as the job in the informal sector. The development of information technology has supported the informal sector to grow and develop. Key word : laborforce, informal sector, information technology